1985
DOI: 10.1063/1.449407
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid electronic properties between the molecular and solid state limits: Lead sulfide and silver halide crystallites

Abstract: Tiny single PbS crystals of ∼25 Å diameter are synthesized and studied optically in low-temperature colloidal solutions. Electron microscopic examination shows a simple cubic rock salt structure with a lattice constant unchanged, within experimental error, from the bulk value. These crystallites lack the near infrared electronic absorption characteristic of bulk PbS. The small crystallite absorbance in the visible rises more steeply than does the bulk absorbance. These results reflect electron and hole localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…As mentioned above, optical constants of nanoparticles can differ from those of the bulk material and in addition depend on the particle size [39][40][41][42][69][70][71][72][73][74][75][76] , which will be evident below with the example of the refractive index. However, the most striking demonstration of related phenomena is probably, as indicated in the preceding section, the color dependence of nanoparticles on the particle size.…”
Section: Influence Of the Particle Size On Optical Properties Of Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, optical constants of nanoparticles can differ from those of the bulk material and in addition depend on the particle size [39][40][41][42][69][70][71][72][73][74][75][76] , which will be evident below with the example of the refractive index. However, the most striking demonstration of related phenomena is probably, as indicated in the preceding section, the color dependence of nanoparticles on the particle size.…”
Section: Influence Of the Particle Size On Optical Properties Of Nanomentioning
confidence: 99%
“…4 91) ) renders this compound attractive for model experiments on the refractive index of polymer nanocomposites. The synthesis of PbS nanoparticles proceeds without problems, and there are many reports on colloidal PbS in dilute solutions 69,70,76,[92][93][94][95] . Nanocomposites containing PbS have also been described.…”
Section: A Pbs-polymer Nanocomposites With High and Ultrahigh Refracmentioning
confidence: 99%
“…By controlling and maneuvering the materials under nanoregime, new pathways are opened to the development of device technologies. Recently Sakthi Sudar Saravanan et al have reported the nanodimensional materials show appreciable quantum confinement effects upon the lowering size of the materials [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the listed advantages from CdS:Mn system, we have chosen the wet chemical precipitation method. Brus et al (1983) [1,2] have reported that the optical absorption behavior of semiconductor nanomaterials are the function of quantum confinement effect. Size dependent optical absorption nature of semiconductor nanosystems strongly follows the confinement theory, which predicts that the effective mass approximation gives suitable solution for weak confinement range (particle radius higher than the Bohr radius).…”
Section: Introductionmentioning
confidence: 99%
“…6-10 Nanoscale Ge 0 semiconductor systems are superior to Si 0 for (i) higher electron and hole mobility, 11 (ii) a larger Bohr exciton radius that yields a more pronounced quantum confinement effect, 12,13-15 and (iii) a predicted nanostructure with direct-bandgap behavior, although bulk Ge 0 is an indirect bandgap material. 16 One reason for the scarce exploration of Ge 0 nanowires as an advanced material is due to the lack of a simple and benign synthetic pathway to this morphology. 17 The previously reported routes cover a myriad of processes, including chemical vapor deposition (CVD), 6, 18 laser ablation, 19 vapor-liquid-solid (VLS) growth, 20 templated supercritical fluid, 21-24 and combination of these techniques.…”
Section: Introductionmentioning
confidence: 99%